Beyond Language Skills: Reframing ESP Pedagogy as Situated Professional Practice through Project-Based and Digital Learning - Suratni Suratni; Refi Yuliana; Ince Dian Aprilyani Azir (Global Education : International Journal of Educational Sciences and Languages, 2026)
In contemporary higher education, English for Specific Purposes (ESP) is increasingly expected to prepare learners for meaningful professional participation rather than isolated linguistic performance. Nevertheless, ESP pedagogy has often remained predominantly skill-oriented, with limited conceptual integration of pedagogical innovations such as project-based learning and digital learning. This study presents a systematic literature review of 40 peer-reviewed studies examining how ESP pedagogy is being reframed as situated professional practice through the integration of project-based and digital learning. Following the process of thematic synthesis, the review provides an examination of what ESP learning is perceived to be, how it is conducted and how it is evaluated in different disciplines and countries. Results show a marked pedagogical transition from a language-centric approach to one that incorporated more authenticity, collaboration and professional concern. Reported learning attainments go beyond language to cover professional capability, digital literacy, autonomous learning and identity development. Project-based learning authenticates language use in professional workflows, and digital learning environments support multimodal communication reminiscent of the way people work today. This review contends that in combination, these perspectives re-conceptualise the pedagogical nature of ESP as a type of applied professional education ’realised’ within particular social, institutional and discipline specific contexts. By synthesizing empirical evidence across settings, the study offers a conceptual reframing of ESP pedagogy and outlines implications for curriculum design, assessment, and future research in higher education and the social humanities.